ANALISIS KUALITAS PELAYANAN PERPUSTAKAAN PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN BENGKAYANG - Naiyun Untung Utama; Pance Doby (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2021)
This research was conducted at Lingga Public Health Center, Kubu Raya Regency. This research is needed to support the use of data techniques carried out by means of the survey method, which is a method of primary data that requires communication between researchers and respondents. The expected objective of this research is to see how the health center services from the variables of direct evidence, reliability, responsiveness, assurance and attention to patient satisfaction. The sampling technique in this research is purposive sampling, which is the taking of the elements that are included in the sample is done deliberately with a note that the sample is representative. And by determining the interval range in This study aims to analyze the effect of service on patient satisfaction at Lingga Public Health Center. Service quality is measured from tangibles or direct evidence, reliability or reliability, assurance or assurance, responsiveness or responsiveness, and empathy or concern. Based on descriptive analysis, the five dimensions have results that are in the good category. The average score for the tangibles was 3.60, or the equivalent of good results. The average score of reliability was 3.90 or equivalent to good results. The average score of the guarantee is 4.01 or equivalent to the good results. The average score of responsiveness was 3.60 or equivalent to good achievement. Also, the average score of empathy is 3.65 or equivalent to good acquisition. The results of the calculations that assess the acquisition as good are also proportional to the satisfaction felt by the patient. This assessment reflects the emotional feelings of patients who are happy with the services provided by the Puskesmas. Keywords: Consumer Perception and Service